Pengaruh Media Pembelajaran Quiziz Terhadap Hasil Belajar dan Keaktifan Belajar Geografi Siswa MAN 2 Bone - Faulil Fahlefi Yusuf; Muhammad Ansarullah S. Tabbu; Sukri Nyompa; Muh. Rais Abidin; Erman Syarif (LaGeografia, 2026)
This study aims to determine the effect of using learning media on the learning outcomes and learning engagement of grade X student at MAN 2 Bone, Tanete Riattang District, Bone Regency. The background of this research stems from the low active participation of students and the variation in learning outcomes in geography subjects, this requiring an innovative digital tearning approach that is interactive and engaging. This research is quantitave with a quasi-experimental design using a pre-test pos-test contro; group model. The research sample consisted of two clases: class X.A as the experimental group using quiziz and class X.B as the control group using conventional teaching methods. Data collection techniques included questionnaires, observations, documentation, and test. Data analysis was conducted using normality test, homogeneity tests, independent t-test, and the mann- Whitney U test. The result showed that the use of quiziz learning media had a significant effect on students’ learning engagemenyt but not on their learning outcomes. The findings indicated that quiziz did not have a significant effect on students’ learning outcomes (p= 0.110> 0.05). Nevertheless, the average score of the experimental class increased from 70.74 to 84.07, while the control class increased from 70.19 to 81.48. conversely, quiziz had a significant effect on students’ learning engagement (p< 0.05), with an increase in the experimental class average from 64.16% to 89.67%, whereas the control class only increased from 63.66 to 79.03 %. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran Quiziz terhadap hasil belajar dan keaktifan belajar siswa di kelas x MAN 2 Bone, Kecamatan Tanete Riattang Kabupaten Bone. Latar belakang penelitian ini berangkat dari rendahnya partisipasi aktif siswa serta variasi hasil belajar pada mata Pelajaran Geografi, sehingga diperlukan inovasi pembelajaran berbasis digital yang interaktif dan menyenangkan. Jenis penelitian ini adalah kuantitatif dengan desain quasi eksperimen menggunakan model pre-test dan pos-test control group design. Sampel penelitian terdiri dari dua kelas yaitu kelas X.A sebagai kelas experimen dengan penggunaan media quiziz dan kelas X.B sebagai kelas kotrol dengan metode pembelajaran konvensional. Teknik pengumpulan data meliputi angket, observasi, dokumentasi, dan tes. Analisis data dilakukan menggunakan uji normalitas, homogenitas, uji t-test independen serta uji Mann-Whitney U. Hasil penelitian menunjukkan bahwa penggunaan media pembelajaran quiziz berpengaruh signifikan terhadap hasil belajar dan keaktifan belajar siswa. Hasil penelitian menunjukkan bahwa Quiziz tidak berpengaruh signifikan terhadap hasil belajar siswa.